2007
DOI: 10.1038/nature06008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide maps of chromatin state in pluripotent and lineage-committed cells

Abstract: We report the application of single molecule-based sequencing technology for high-throughput profiling of histone modifications in mammalian cells. By obtaining over 4 billion bases of sequence from chromatin immunoprecipitated DNA, we generated genome-wide chromatin state maps of mouse embryonic stem cells, neural progenitor cells and embryonic fibroblasts. We find that lysine 4 and lysine 27 tri-methylation effectively discriminate genes that are expressed, poised for expression, or stably repressed, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

240
4,057
18
24

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,770 publications
(4,380 citation statements)
references
References 49 publications
240
4,057
18
24
Order By: Relevance
“…This suggests that opo has a complex regulatory input, as previously reported for other developmental genes 40 . For each CNE, we then examined the co-occurrence of the predictive enhancer epigenetic marks H3K4me1 and H3K27ac, as determined in previous chromatin immunoprecipitation (ChIP)-Seq studies in human cell lines 41,42 and, for their homologous regions, in zebrafish embryos 43 . These analyses revealed that a large majority of the identified CNEs (21 out of 23) overlap with regions labelled with at least one epigenetic mark, either in human cell lines, zebrafish embryos or both (Supplementary Table 2), suggesting that these conserved regions may act as enhancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that opo has a complex regulatory input, as previously reported for other developmental genes 40 . For each CNE, we then examined the co-occurrence of the predictive enhancer epigenetic marks H3K4me1 and H3K27ac, as determined in previous chromatin immunoprecipitation (ChIP)-Seq studies in human cell lines 41,42 and, for their homologous regions, in zebrafish embryos 43 . These analyses revealed that a large majority of the identified CNEs (21 out of 23) overlap with regions labelled with at least one epigenetic mark, either in human cell lines, zebrafish embryos or both (Supplementary Table 2), suggesting that these conserved regions may act as enhancers.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 conserved CNEs were selected within the opo locus using VISTA Browser 65 and taking as a reference the human genome (NCBI36/hg18) and the default parameters (Z100 bp and Z70% identity). The presence of predictive epigenetic marks for enhancer activity 66 that overlap opo-associated CNEs was evaluated using available data from human cell lines 41,42 and zebrafish embryos 43 . As a reference, four non-conserved elements marked with H3K4me1 and H3K27ac signals in human cell lines were also tested in our enhancer screening.…”
Section: Methodsmentioning
confidence: 99%
“…Third, remarkably and paradoxically, formation of heterochromatin actually depends on a degree of transcription, which contributes to heterochromatinization through the RNAi pathway [4]. Consistent with this, recent genome-wide analyses have shown that virtually all DNA nucleotides of the human genome are, to some degree, transcribed into RNA [13][14][15]. Indeed, telomeric heterochromatin was recently shown to be transcribed [16,17].…”
Section: The Dynamic and Stochastic Properties Of Chromatinmentioning
confidence: 89%
“…H4K20me1 is associated with facultative heterochromatin (Fang et al, 2002;Martens et al, 2005;Sims et al, 2006), and the inactive X chromosome (Kohlmaier et al, 2004). In contrast, H4K20me3 marks constitutive heterochromatin (Schotta et al, 2004;Mikkelsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%